Primary hypophysitis: Experience of a Single Tertiary Center - Korkmaz, Ozge Polat; Sahin, Serdar; Ozkaya, Hande Mefkure; Apaydin, Tugce; Durmaz, Emine Sebnem; Haliloglu, Ozlem; Durcan, Emre; Kadioglu, Pinar (Experimental and Clinical Endocrinology & Diabetes, 2019)
Purpose The authors review the clinical outcomes of patients with primary hypophysitis (PH).Methods Patients with PH who were followed up between 2007 and 2018 at our clinic were evaluated. Clinical, endocrinologic, pathologic, radiologic findings and treatment modalities were assessed.Results Seventeen patients with PH were assessed. The median follow-up was 24 (range, 6–84) months. Histologic confirmation was available in 8 patients (6 lymphocytic hypophysitis, 1 lymphocytic-granulomatous hypophysitis, 1 xanthomatous hypophysitis). None of the cases were diagnosed after pregnancy. Two patients had an autoimmune disease. The most commonly seen symptom was headache. The most common anterior pituitary deficiencies were hypocortisolemia and hypothyroidism. The radiologic findings of the patients at the time of diagnosis revealed various results including space-occupying lesion (41.2%), loss of posterior hypophysis bright spot (47.1%), pituitary stalk thickening (41.2%), uniform contrast enhancement (17.6%), partially empty sella (11.8%), optic chiasm compression (11.8%). The most frequent initial treatment modality was observation. Ten patients who were followed up conservatively had no endocrinologic deterioration; additional treatment was not needed in 8 of these 10 patients. The second most frequent initial treatment modality was pituitary surgery. Five patients received steroid treatment. We found serious adverse effects during steroid treatment in 3 of 5 (60%) patients; unilateral avascular necrosis of the femoral head (n=2), diabetes mellitus(n=1).Conclusion Correctly diagnosing PH and giving appropriate treatment is challenging. It is unclear whether active treatment with steroids improves clinical outcomes. The serious adverse effects of steroids are also taken into account. Observation, surgery and/or radiotherapy can be appropriate treatment modalities for selected patients.
Keywords: hypophysitis; steroid treatment; surgery; observation